GROWTH PROFILE ANALYSIS OF OIL PALM BY USING SPOT 6 THE CASE OF NORTH SUMATRA - Ita Carolita; J. Sitorus; Johannes Manalu; Dhimas Wiratmoko (International Journal of Remote Sensing and Earth Sciences, 2015)
Oil Palm (Elaeis guineensis Jack.) is one of the worldâ€™s most important tropical tree crops. Its expansion has been reported to cause widespread environment impacts. SPOT 6 data is one of high resolution satellite data that can give information more detail about vegetation and the age of oil palm plantation. The objective of this study was to analyze the growth profile of oil palm and to estimate the productivity age of oil palm. The study area is PTP N 3 in Tebing Tinggi North Sumatera Indonesia.Â The method that used is NDVI analysis and regression analysis for getting the model of oil palm growth profile. Data from the field were collected as the secondary data to build that model. The data that collected were age of oil palm and diameters of canopy for every age.Â Â Results indicate that oil palm growth can be explained by variation of NDVI with formula y = -0.0004x2 + 0.0107x + 0.3912, where x is oil palm age andÂ Y is NDVI of SPOT, with RÂ² = 0.657. This equation can be used to predict the age of oil palm for range 4 to 11 years with R2 around 0.89.